The first wood gnat (Diptera: Anisopodidae) from the Oligocene of Luberon (France) - Hebert, Florence; Boderau, Mathieu; Muller, Valerie Ngo; Coster, Pauline; Nel, Andre (Zootaxa, 2025)
The anisopodid Sylvicola vacherensis sp. nov. is described from the Oligocene of Luberon (France) on the basis of a unique specimen from the locality of Pichovet (Luberon), well known for its very rich and diverse vertebrate assemblage. The Anisopodidae are very rare in the lacustrine paleolakes of Provence, despite their larvae are saprophagous, while the bibionid flies, with very similar biology, are extremely frequent and dominate the insect assemblages.